Role of Geology in Groundwater Potential Zoning Using Remote Sensing and GIS: A Case Study of Neem Ka Thana, Rajasthan (Prakriti - The International Multidisciplinary Research Journal, 2026)
Geological and geomorphological factors significantly influence groundwater supply in semi-arid areas like Neem Ka Thana, Rajasthan (Wikipedia, 2025). This study highlights how geology, including lithology, soil properties, and structural aspects, helps define groundwater potential zones. The BhuKosh and WRIS databases are used to generate thematic layers for the study, which include geology, geomorphology, lithology, soil depth, and soil texture (Bhuvan, 2025; WRIS, 2024). To evaluate their impact on groundwater storage and transport, structural elements such faults, folds, and lineaments were mapped. These datasets first preprocessing offers information on subsurface flow behaviour, storage capacity, and recharge potential. The results demonstrate that in hard rock terrains, lithological variances, soil depth, and geomorphic units are important factors that influence groundwater availability (Strahler, 1957; Patel et al., 2012). This framework lays the foundation for subsequent multi-criteria groundwater potential mapping.
Keywords: Geology; Geomorphology; GIS; Groundwater potential; Lithology; Neem Ka Thana; Rajasthan; Remote sensing; Soil depth; Soil texture